FLOSS and digital inclusion in Brazil: a literature review - Lisboa, Flávio Gomes da Silva (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware), 2022)
This article is the first part of a broad research on digital inclusion policies in Brazil. In particular, this research aims to find out how free and open source software (FLOSS) has been used in digital inclusion actions. To support this work, we conducted a literature review, with no starting date limit, searching for scientific production that relates digital inclusion with the concepts of free software or open source software. We found 66 works, published between 2003 and 2022, which include journal articles, conference papers, bachelor, specialist and master dissertations, doctoral theses and books. These papers were produced by authors from 37 different research institutions, within 28 programs or courses. It was possible to highlight some categories in this preliminary analysis, such as accessibility, policies, and “telecentros” (community technological centers), but a deeper analysis is needed to better understand the contributions of this scientific production.